Robust controller design for small pressurized water reactors using non-smooth optimization. (January 2022) - Wang, Pengfei; Jiang, Qingfeng; Wan, Jiashuang; Wu, Shifa
Highlights: Sensitivity analysis is conducted to determine SPWR uncertainty parameters. Robust controller design method for SPWRs is proposed using non-smooth optimization. Robust design of SPWR controllers is transformed into constrained minimization. Designed SPWR controllers have strong robustness under large uncertainties. Abstract: The flexible operating conditions of small pressurized water reactors (SPWRs) under parameter uncertainties require highly robust control systems. This paper presents a robust controller design for an SPWR using non-smooth optimization. First, nonlinear mathematical models of the SPWR nuclear steam supply system were adopted and linearized to obtain the corresponding transfer function models. Then, sensitivity analysis of the SPWR physical and thermodynamic parameters was conducted to determine the critical uncertainty parameters for the robust controller design. Subsequently, the reactor power and steam generator feedwater robust control systems were designed under large uncertainties in the identified critical parameters. Finally, simulation studies of typical transients for the SPWR under high- and low-speed operating conditions of the main pump were performed. The results indicate that the designed robust control systems for the SPWR exhibit good performance and excellent robustness under large parameter uncertainties during various load change transients.